UPAYA MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN MELALUI BLENDED LEARNING DI KELAS V SD MUHAMMADIYAH PURWOKERTO - Ninda Nur Afifah; Dedy Irawan; Cicih Wiarsih (Renjana Pendidikan Dasar, 2022)
Abstract: Reading skills are skills to dig up information from various written and oral sources. The study used a Blended Learning model that combines two face-to-face and online learning. This classroom action research aims to improve comprehension reading skills in learners. This research was conducted in May 2021, in class V of Muhammadiyah Purwokerto Elementary School. This study is a Class Action Study with two cycles consisting of two meetings in one cycle. This research procedure refers to the kemmis &Mc. Taggart model which includes planning, execution of actions, observation, and reflection. The research subject was a student of class V muhammadiyah purwokerto elementary school with a total of 23 students consisting of 16 male students and 7 female students. The instruments used are teacher and student observation sheets, performance assessment of reading comprehension orally, and face-to-face and online evaluation sheets of learners. The results of this study showed that the improvement of comprehension reading skills in cycle I reached a learning completion of 55.55% and in cycle II rose to 77.78%. It can be concluded that the application of blended learning models can improve reading skills in learners. With the COVID-19 pandemic, the Ministry of Education in Indonesia issued a policy that is to dissolve schools and replace the teaching and learning process by using online or online systems. Keywords: Comprehension reading skills, blended learning, classroom action research, pandemic covid-19